Nationalism and Internationalism in Liberalism, Marxism and Islam: By Tahir Amin. Islamabad: IIIT, 1991. xxxii + 106 pp. (American Journal of Islam and Society, 1992)
Professor Amin, who teaches international relations at Quaid-i-AzamUniversity in Islamabad, has provided us with a short but insightfulanalysis of twentieth-century writings from the Liberal, Marxist, andIslamic traditions on the issue of "nationalism versus internationalism."Pointing out that Western writings treat the "nation-state" as "a universalform," he presents two main arguments: a) nationalism emerged from"Western liberal culture" and is now "seriously challenged by a varietyof communitarian internationalisms," of which Islamic revivalism is themost important in the Islamic world (p. 5), and b) Islamic revivalismoftenmisunderstood as being a backward-looking "fundamentalism" -is"a reaction against Liberal and Marxist internationalism which are seenas the two imperialist ideologies of the West" (p. 6).Amin briefly states the essence of the three traditions-the Liberalbelief in nationalism as natural, with "world unity [envisaged as emerging]through the prism of nation-states" (p. 7); the Marxist goal of a "classlessworld society" (p. 7); and the Islamic idea of all "believers . . . belong [ing] to one global community, the ummah" (p. 10). Insisting that thedialogue among the three trends is facilitated by understanding all of them"from within and through their main spokesmen" (p. 10), he proceeds witha chapter on the representative literature of each. Each chapter is dividedinto three sections: traditional writers, modernization theorists, and postmodernizationtheorists.Perhaps reflecting the author's Western education, the book's longestchapter is the one on Liberalism. He begins with Toynbee, whom hedescribes as "an internationalist par excellence in the Western communitariantradition" (p. 13). Three other Liberal writers are categorized as"traditional"-E. H. Carr, Hans Kohn, and Carleton Hayes. Under the designationof modernization theorists, Amin deals with Karl Deutsch andErnest Gellner, while the section on post-modernization theorists looksmainly at Walker Conner and A. D. Smith.In the chapter on Marxism, Amin analyzes Marx and Engels as "traditionalwriters." Lenin is classified as a "modernization theorist," while ...